2011
DOI: 10.1039/c0cc03676e
|View full text |Cite
|
Sign up to set email alerts
|

Concise synthesis of catechin probes enabling analysis and imaging of EGCg

Abstract: A concise synthesis of APDOEGCg (3) was accomplished. Due to the reactivity of its amine group, the compound could be easily converted to the fluorescein probe 21 and immunogen probe 22 efficiently. We then demonstrated the usefulness of the probes for imaging studies and the generation of antibodies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…36, 37 Coupling of the alcohols ( 9a–d ) with aromatic acids 12–16 enlisting 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide (EDCI) and 4-dimethylaminopyrine (DMAP) gave the corresponding esters, 10a–t . 38 Hydrogenolysis of 10k–t with palladium/carbon and hydrogen gas gave 11a–j in high yield.…”
Section: Resultsmentioning
confidence: 99%
“…36, 37 Coupling of the alcohols ( 9a–d ) with aromatic acids 12–16 enlisting 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide (EDCI) and 4-dimethylaminopyrine (DMAP) gave the corresponding esters, 10a–t . 38 Hydrogenolysis of 10k–t with palladium/carbon and hydrogen gas gave 11a–j in high yield.…”
Section: Resultsmentioning
confidence: 99%
“…Although some studies have visualized its tissue distribution by fluorescence imaging, cerium chloride staining, immunostaining, and radioactive labeling assays, [74][75][76][77] spatiotemporal information has been lacking because of the absence of an analytical technique that can easily detect the localization of the naïve polyphenol. Conventional molecular imaging generally requires labeling steps that are time-consuming, expensive, and laborintensive.…”
Section: Biotransformation and Distribution Of The Green Tea Polymentioning
confidence: 99%
“…However, there is little information about the biodistribution of catechins after their intake; because the synthesis of artificial EGCG is quite complicated, and the detection of catechins or their metabolites in the body is difficult. On the other hand, we recently succeeded in developing a novel method for the synthesis of EGCG and its derivatives, and investigated the intracellular distribution of this synthetic EGCG in human umbilical vein endothelial cells (HUVEC) by using fluorescence-labeled EGCG [7]. The results indicated that a portion of this EGCG accumulates in the mitochondria of these cells, suggesting that mitochondrial dysfunction might be involved in the anti-angiogenic effect of EGCG [7].…”
Section: Introductionmentioning
confidence: 99%